Increasing The Effectiveness Of 20 WP Solar Panel Power Absorption Using Three Angle Variations Based On The Effect Of Temperature Changes In Padang City - Yulianis; Mairizwan; Yulkifli (Universitas Negeri Padang, 2023)
In this paper, a system has been successfully designed to measure the effectiveness of solar panel power absorption with three variations in location and temperature changes in the city of Padang. The performance specifications for this system use three 20-watt solar panels with varying angles of 50°, 65°, and 75°. Use of the INA219 sensor, DS18B20 sensor, and BH1750 sensor, which measure power, temperature, and light intensity parameters. The system uses a Bluetooth serial terminal as a data logger and data storage device. The design specifications for sensor accuracy are 97.5% for current, 98.3% for voltage, 98.7% for temperature, and 99.7% for light intensity. Sensor accuracy is 99.905% for current, 99.996% for voltage, 99.838% for temperature, and 99.383% for light intensity. Based on these results, the smart garden tool design can work well. The results of the increase for three variations of angles at three locations in the city are: Power absorption at an angle of 50° at 3 different locations obtained power absorption of 3447.07 Watts (urban), 2566.3 Watts (hills), and 2461 Watts (beach). Power absorption at an angle of 65 ° at 3 different locations obtained power absorption of 2324.67 Watts (urban), 1679.35 Watts (hills), and 1779.03 Watts (beach). Power absorption at an angle of 75° at 3 different locations obtained power absorption of 2162.16 Watts (urban), 1687.85 Watts (hills), and 1799.58 Watts (beach). From the measurement results, it can be concluded that increasing the effectiveness of solar panel energy harvesting can be done in urban locations at an angle of 50°.